The Role of PCSK9 Inhibition and Small Interference RNA (siRNA) in The Management of Dyslipidaemia and ASCVD - Santoso, Anwar; Dwiputra, Bambang (The Indonesian Biomedical Journal, 2026)
Compelling evidence linking low-density lipoprotein cholesterol (LDL-C) reduction to decreased mortality has positioned LDL-C lowering as a central strategy in the prevention of atherosclerotic cardiovascular disease (ASCVD). Nonetheless, despite widespread statin use, an estimated 10–20% of individuals at high or very high cardiovascular risk fail to attain guideline-recommended LDL-C targets. This persistent treatment gap underscores the need for more potent and durable lipid-lowering strategies, particularly among patients with familial hypercholesterolemia (FH) and those with established ASCVD whose LDL-C levels remain inadequately controlled despite optimized combination therapy, including statins, ezetimibe, and proprotein convertase subtilisin–kexin type 9 (PCSK9) monoclonal antibodies. Inclisiran, a first-in-class small interfering RNA agent, addresses this unmet need by selectively inhibiting hepatic synthesis of PCSK9, thereby enhancing low-density lipoprotein receptor (LDLR) recycling and accelerating LDL-C clearance. Nevertheless, thus far, no cardiovascular outcome trial (CVOT) has been available. With a convenient twice-yearly dosing regimen, inclisiran consistently achieves LDL-C reductions exceeding 50% and demonstrates a favourable tolerability profile, offering an effective and patient-friendly advancement in dyslipidaemia management.KEYWORDS: dyslipidaemia, ASCVD, PCSK9 inhibition, siRNA, inclisiran